RELEVANSI SISTEM BIOPORI DALAM UPAYA PENANGANANAN DAN PENCEGAHAN BANJIR MELALUI ANALISIS BIBLIOMETRIC - Rochman, Abdul; Sutryani, Heni; Dewi, Astri Kustina; Nurlukman, Adie Dwiyanto; Fadli, Yusuf (Universitas Muhammadiyah Tangerang, 2023)
Increased studies and research regarding the effectiveness of the biopore system in handling and mitigating floods have been carried out and have shown a positive impact on the effectiveness of the system. This research tries to carry out a bibliometric analysis on the topic of biopores and their relationship to flooding. The research method used in this research is a qualitative method with a bibliographic approach. Data analysis was carried out using Vosviewer on 500 articles related to